2016
DOI: 10.1016/j.jfoodeng.2015.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Drying characteristics and quality of grape under physical pretreatment

Abstract: Grape drying is a slow and energy intensive process because the waxy peel has low permeability to moisture.\ud Therefore, peel chemical and physical pretreatments are considered before drying in order to facilitate\ud water diffusion. However, they cause heterogeneity in the waxes removal and problems during\ud shelf-life.\ud In this paper an alternative abrasive pretreatment of grape peel, for enhancing the drying rate and preserving\ud the samples, was applied to Red Globe grapes. Convective drying experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
107
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 42 publications
8
107
0
2
Order By: Relevance
“…These results agreed with earlier studies that reported the drying of grape seeds could be accurately predicted by using Henderson–Pabis model (Roberts et al, ). Another study by Adiletta et al () stated that the logarithmic model was the best model for drying predictions of physically pretreated grapes at temperatures (313.15–333.15 K). Several studies have been carried out on drying behavior of different grape variety seeds using thin layer models; Roberts et al () investigated the drying behavior of three grape seed varieties (Riesling, Cab Franc, and Concord) at different temperatures (313.15–333.15 K) and proposed the different drying models (Riesling and Cab Franc seeds–Lewis model; Concord seeds–Page model) for different grape variety, which demonstrated the influence of grape variety to predict the drying model.…”
Section: Resultsmentioning
confidence: 99%
“…These results agreed with earlier studies that reported the drying of grape seeds could be accurately predicted by using Henderson–Pabis model (Roberts et al, ). Another study by Adiletta et al () stated that the logarithmic model was the best model for drying predictions of physically pretreated grapes at temperatures (313.15–333.15 K). Several studies have been carried out on drying behavior of different grape variety seeds using thin layer models; Roberts et al () investigated the drying behavior of three grape seed varieties (Riesling, Cab Franc, and Concord) at different temperatures (313.15–333.15 K) and proposed the different drying models (Riesling and Cab Franc seeds–Lewis model; Concord seeds–Page model) for different grape variety, which demonstrated the influence of grape variety to predict the drying model.…”
Section: Resultsmentioning
confidence: 99%
“…This increased the drying rate during raisin production (19). However, the wax layer has been reported to provide a barrier to prevent against invasion of pathogenic organisms (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, various chemical-dipping pretreatments had been used, including potassium carbonate-ethyl oleate, sodium hydroxideethyl oleate, and sodium hydroxide-potassium carbonate-ethyl oleate (17,18). The dipping pretreatment not only reduces the drying time, increasing the economic benefit, but also improves the color, flavor, and nutritional quality of dried vine fruit (17,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-treatment step was achieved to prevent the change in qualities of many processed food. Blanching with hot water and soaking in chemical solutions were extensively used for solving the change of dried product [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%